Isolation and Identification of Escherichia coli and Salmonella typhimurium from Sheep in Baghdad city: الاء طه حنون و اكرام عباس عبود السامرائي - Hanoun, Alaa Taha Taha; Al-Samrraae, Ikram Abbas Aboud (The Iraqi Journal of Veterinary Medicine, 2019)
One hundred fifty fecal samples of sheep were collected from September, 2017-March, 2018 in Baghdad city areas (Abu-Grab zone, Dora zone, Saydyia zone, Arab jbure zone, Al-Usfia zone, Al-Fudhalia zone and College Veterinary medicine –University of Baghdad). Samples were cultured on MacConkey and Eosine Methylene Blue agar for E.coli isolation, Xylose Lysine Deoxycholate and Salmonella –Shigella agar for S. typhimurium isolation. Results showed high percent (78.57%) of infection in female of E.coli than 68.42% in Salmonella typhimurium. E.coli was recovered with an infection rate 93.33% in Al-Fudhalia area, and S. typhimurium with an infection rate 12.66% in Arab Jbur. Also, the results showed an infection rate of E.coli 78.75% (110/140) and 21.43% (30/140), and S. typhimurium was recovered in 68.42% (13/19) and 31.58% (6/19) in females and males respectively .